Tepe Gryashan. Late Chalcolithic Pottery from the Region of Sanandaj, Western Iran - Mohammadi Ghasrian, Sirvan; Zamani Dadaneh, Morteza; Colantoni, Carlo; Bruun Skuldbøl, Tim Boaz (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
This paper presents the first results of a study of pottery evidence from a new archaeological project being conducted at the site of Tepe Gryashan located in the province of Kurdistan, western Iran. The collected pottery, including Sprig ware-like sherds and Flint-scraped Coba bowls, are rare evidence of material culture contact with northern Mesopotamia from the early Late Chalcolithic period.